2014
DOI: 10.1186/1471-2229-14-93
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max) expansin gene superfamily origins: segmental and tandem duplication events followed by divergent selection among subfamilies

Abstract: BackgroundExpansins are plant cell wall loosening proteins that are involved in cell enlargement and a variety of other developmental processes. The expansin superfamily contains four subfamilies; namely, α-expansin (EXPA), β-expansin (EXPB), expansin-like A (EXLA), and expansin-like B (EXLB). Although the genome sequencing of soybeans is complete, our knowledge about the pattern of expansion and evolutionary history of soybean expansin genes remains limited.ResultsA total of 75 expansin genes were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(204 citation statements)
references
References 106 publications
(127 reference statements)
12
155
0
8
Order By: Relevance
“…They play important roles in the regulation of plant growth and development processes, such as root development, leaf growth, fruit ripening, seed germination, penetration of pollen tubes, etc. In this study, we identified 42 MtEXP genes from M. truncatula genome by bioinformatics analysis, which was similar to previous reports in Arabidopsis, [3] rice, [27] soybean [28] and poplar, [29] and indicated that expansin genes are highly conservative in plants. [17,30] …”
Section: Identification and Classification Of Mtexp Genes In M Truncsupporting
confidence: 71%
“…They play important roles in the regulation of plant growth and development processes, such as root development, leaf growth, fruit ripening, seed germination, penetration of pollen tubes, etc. In this study, we identified 42 MtEXP genes from M. truncatula genome by bioinformatics analysis, which was similar to previous reports in Arabidopsis, [3] rice, [27] soybean [28] and poplar, [29] and indicated that expansin genes are highly conservative in plants. [17,30] …”
Section: Identification and Classification Of Mtexp Genes In M Truncsupporting
confidence: 71%
“…Expansin genes were distributed on the ten chromosomes (A) of B. rapa with different densities. Two unmapped genes BrEXPA39 and BrEXPB9 were located on Scaffold000317 (gene position: 22,499-24,350) The Arabidopsis, poplar, rice, and last common ancestor data were obtained from ; the soybean, common bean, and Medicago truncatula data were obtained from Zhu et al (2014); and the grapevine data were obtained from DeSanto et al and Scaffold000111 (gene position: 290,653-291,849), respectively. The maximum number of expansin genes was found on A03 (n = 8), followed by A02 (n = 7) and A05 (n = 7).…”
Section: Synteny Analysis and Chromosomal Mapping Of Brexpsmentioning
confidence: 99%
“…Whole genome screening has been applied to explore several species-specific structural features of expansins in A. thaliana , rice (Oryza sativa; , poplar (Populus trichocarpa; Sampedro et al 2006), grapevine (Vitis vinifera;DeSanto et al 2013) and soybean (Glycine max; Zhu et al 2014). These genome-wide identifications and comparisons among different species have provided rich resources for the evolutionary analysis of expansins.…”
Section: Introductionmentioning
confidence: 99%
“…They are 768 bp in length, encoding 255 amino acids. When compared with the classification system proposed by Zhu et al (2014), GmEXP1 is identical to GmEXPA37, an α-expansin subfamily, which is located on chromosome 17. This result is consistent with the soybean mRNA genetic map constructed by Libault et al (2010).…”
Section: Cloning Of the Gmexp1 Gene From Vietnamese Soybean Cultivarsmentioning
confidence: 99%
“…The GmEXP1 from chromosome 17 is 1491 nucleotides long, containing 3 exons and 2 introns. The coding region is 768 nucleotides in length, encoding α-expansin with 255 amino acids (Kende et al, 2004;Zhu et al, 2014), and consists of three regions: a signaling region, an active region similar to endoglucanase, and the pollen allergen region for substrate adhesion (Wu et al, 2001). When the cell wall reaches a pH growth level of 4.5-6.0 and the ratio of expansin and cell wall (on a dry mass basis) is 1:10,000, the expansin will cause cellular structural changes by sticking, breaking links between polysaccharide components (including pectin and hemicellulose), and loosening the polymer network.…”
Section: Introductionmentioning
confidence: 99%